Early Cretaceous adakitic magmatism in the Dachagou area, northern Lhasa terrane, Tibet: Implications for slab roll-back and subsequent slab break-off of the lithosphere of the Bangong–Nujiang Ocean. (1st January 2015) - Wu, Hao; Li, Cai; Xu, Mengjing; Li, Xingkui
Highlights: Early Cretaceous granodiorites were recognized in northern Lhasa terrane. The granodiorites are divided into high-K and low-K types. The high-K type is product of slab roll-back. The low-K type is product of the subsequent slab break-off. Abstract: The late Mesozoic geodynamic evolution of the Lhasa terrane (Tibet) remains controversial due to a lack of systematic geochemical and chronological data. Here we present the results of geochemical and zircon U–Pb geochronological studies of two granodiorite plutons in the Dachagou area of the northern Lhasa terrane. The zircon U–Pb dating yielded magmatic crystallization ages of 104 and 117 Ma, indicating pluton emplacement in the Early Cretaceous. On the basis of their K2 O contents, the granodiorites can be divided into low-K calc-alkaline granodiorites (LKG, 104 Ma) and high-K calc-alkaline granodiorites (HKG, 117 Ma), and both types are characterized by the adakitic signatures of high Na2 O and Sr contents, low Yb and Y abundances, and high Sr/Y ratios. The fact that the LKG and HKG formed at different times and have different geochemical characteristics suggests different petrogenetic mechanisms. Specifically, the LKG were generated by the interaction of an oceanic-slab-derived melt with enriched mantle, while the HKG were derived via the partial melting of the lower crust followed by hybridization with a significant amount of sediment and a minor amount of mantle. Based on these data and the regional tectonic setting, we propose that the LKG and HKG resulted from different geodynamic mechanisms: the HKG were the product of slab roll-back, while the LKG resulted from the subsequent slab break-off during the southwards subduction of the Bangong–Nujiang Ocean seafloor.